The role of first trimester fetal heart rate in the prediction of gestational diabetes: A multicenter study. (December 2019) - Sirico, Angelo; Lanzone, Antonio; Mappa, Ilenia; Sarno, Laura; Słodki, Maciej; Pitocco, Dario; Zullo, Fulvio; Maruotti, Giuseppe Maria; Rizzo, Giuseppe
Abstract: Objective: Early pregnancy models for prediction of GDM have been proposed, mostly using anamnestic and biochemical parameters. The aim of our study was to evaluate the strength of association of first trimester fetal heart rate (FHR) in predicting the development of gestational diabetes (GDM). Study design: We considered in our analysis singleton non-diabetic pregnant women who underwent a first trimester screening at 11–14 weeks. Data on maternal age, BMI, cigarette smoking, NT, FHR, CRL, DV-PVI, β-hCG and PAPP-A were included in the analysis. Multivariate logistic regression analysis was used to estimate the association between maternal characteristics and first-trimester ultrasound measurements and GDM. We evaluated the efficacy of different models for the prediction of GDM. Results: We considered 603 women, of whom 199 (33%) were subsequently diagnosed with GDM. ROC analysis showed that first trimester FHR was highly predictive of GDM (AUC 0.809, 95% CI 0.769–0.849, p < 0.001). At FPR of 20%, first trimester FHR had a detection rate of 65.2% for GDM (positive likelihood ratio: 3.26; negative likelihood ratio: 0.43), which increased to 89.5% at FPR of 40% (positive likelihood ratio: 2.24; negative likelihood ratio: 0.17). When considering as threshold 162 bpm, FHR showed detection rate of 76.9%, specificity of 67.1% and negative predictive value of 85.5% for GDM. Conclusion: This is the first study to highlight the potential role of first trimester FHR as early predictor of GDM. In our cohort, a threshold of 162 bpm has shown high detection rate and NPV for GDM.